2019
DOI: 10.1371/journal.pone.0211985
|View full text |Cite
|
Sign up to set email alerts
|

Mobile genomic element diversity in world collection of safflower (Carthamus tinctorius L.) panel using iPBS-retrotransposon markers

Abstract: Safflower ( Carthamus tinctorius L.) is a multipurpose crop of dry land yielding very high quality of edible oil. Present study was aimed to investigate the genetic diversity and population structure of 131 safflower accessions originating from 28 different countries using 13 iPBS-retrotransposon markers. A total of 295 iPBS bands were observed among which 275 (93.22%) were found polymorphic. Mean Polymorphism information content (0.48) and diversity parameters including mean effective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 50 publications
1
37
2
1
Order By: Relevance
“…Mean gene diversity (0.22) resulted in this study was found higher than the reported by earlier studies [25,48,50] and thus explains the presence of higher diversity in studied germplasm. Shannon's information index is an important criterion to understand the variation as it distinguishes the genetic diversity in a population combining abundance and evenness [51]. Mean Shannon's information index (0.35) was found greater than the reported by earlier studies using the same molecular marker [25,50].…”
Section: Genetic Diversity and Population Evaluation For Turkish Laurmentioning
confidence: 68%
See 2 more Smart Citations
“…Mean gene diversity (0.22) resulted in this study was found higher than the reported by earlier studies [25,48,50] and thus explains the presence of higher diversity in studied germplasm. Shannon's information index is an important criterion to understand the variation as it distinguishes the genetic diversity in a population combining abundance and evenness [51]. Mean Shannon's information index (0.35) was found greater than the reported by earlier studies using the same molecular marker [25,50].…”
Section: Genetic Diversity and Population Evaluation For Turkish Laurmentioning
confidence: 68%
“…Previous studies have proven iPBS-retrotransposon a highly reproducible, robust and trustable marker system [22,23,40,41]. Our earlier studies in wild emmer [8], pea [24], tobacco [25], common bean [48], pepper [50] and safflower [51] also found this marker system highly robust, and trustable, which can be used for the investigation of genetic diversity in any crop. Similarly, Mehmood et al [41] also found this marker system highly reproducible, robust and trustable.…”
Section: Polymorphism In Turkish Laurel Germplasm Revealed By Ipb-retmentioning
confidence: 91%
See 1 more Smart Citation
“…Advancement in molecular marker technologies has boosted the success level of breeding activities for various crops worldwide (Nadeem et al, 2018b). Retrotransposons comprise a large fraction of most plant genomes, and their replication generates genomic diversity, which can be exploited as an excellent source of molecular markers for genetic diversity assessment in various crops (Andeden et al, 2013;Ali et al, 2019). Retrotransposon-based markers can be effectively used to address microevolutionary questions, at the intragenus or intraspecific level, as their insertion into the genome generates frequent and polymorphic DNA sites (Kalendar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Safflower (Carthamus tinctorius L.) is an underutilized oilseed crop and belongs to the family Asteraceae (Knowles, 1989;Ali et al, 2019). It is known as one of the oldest crop plants grown under dry and hot climatic conditions of the Middle East, which is its origin and diversity center (Knowles and Ashri, 1995).…”
Section: Introductionmentioning
confidence: 99%